2016
DOI: 10.1186/s12970-016-0138-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute pre-workout supplementation on power and strength performance

Abstract: BackgroundConsumption of pre-workout dietary supplements by both recreational and competitive athletes has increased dramatically in recent years. The purpose of this study was to determine the acute effects of a caffeine-containing pre-workout dietary supplement on various measures of performance including anaerobic power, upper and lower body power, and upper body strength in recreationally trained males.MethodsThirteen males (mean ± SD age = 24 ± 6 yrs; height = 180.3 ± 5 cm; body mass = 83.4 ± 9 kg) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 34 publications
1
35
1
Order By: Relevance
“…PWS claim to enhance exercise performance, reduce perception of fatigue, promote focus and for many, assist body fat loss. While only a few studies have been conducted to determine the efficacy of PWS on strength and power, isolated ingredients such as caffeine have received considerable scientific attention, indicating likely ergogenic effects . As such, many PWS promote the inclusion of caffeine as a primary active ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…PWS claim to enhance exercise performance, reduce perception of fatigue, promote focus and for many, assist body fat loss. While only a few studies have been conducted to determine the efficacy of PWS on strength and power, isolated ingredients such as caffeine have received considerable scientific attention, indicating likely ergogenic effects . As such, many PWS promote the inclusion of caffeine as a primary active ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…When the literature concerning this aspect is examined, it is observed that there are studies with respect to the effect of pre-workout nutritional supplement on athlete's aerobic and anaerobic performances [5, 8 -11]. To illustrate, Martinez et al [9] investigated the acute effects of caffeine-containing pre-workout nutritional supplement on anaerobic power for men who work out recreationally, and reported that these supplements lead to significant improvements in the values of anaerobic peak power and mean power. In a similar study, Jagim et al [10] examined the effects of multi-ingredient pre-workout ingestion on strength performance, lower body power and anaerobic capacity in resistance trained collegeaged men, and concluded that this supplement improved the mean power in anaerobic running capacity test.…”
Section: Introductionmentioning
confidence: 99%
“…This supplement has been shown to increase blood levels of ATP [22], increase exercise levels in sedentary individuals from a single dose [23], and enhance responses to chronic resistance training [24]. The supplement Huperzine has been shown to have positive effects on brain function, specifically decreasing cognitive deficits and oxidative stress in the rodent model after hypobaric hypoxia [25], and has been shown in conjunction with other supplements to enhance upper body strength endurance performance [6] and anaerobic sprint performance [26].…”
Section: Introductionmentioning
confidence: 99%